No Sale: a history of successful failure(s) at teaching the Holocaust to Israel’s Palestinian Arab citizenry, 1996 to the present. - Tyndall, Andrea G. (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
In the past 25 years, there have been three distinct efforts by Yad Vashem to teach the Holocaust to Israel’s Arab citizenry. All three programs failed miserably. In this paper, I analyse these different programs so as to identify the systemic causes of Yad Vashem’s sole educational failure (s) in teaching the Holocaust to its population. This paper argues that these programs were seen as failure(s) because they did not achieve the stated educational goals. This research supports the claim that these very failures were in fact successes in that they maintained the core beliefs that created the continuing conflict between Jewish and Arab citizens in the first place. These failures were, in fact, successful components in maintaining an intractable conflict between the majority and minority populations. These findings rest upon two bodies of research materials. The first is primary sources gathered from Yad Vashem and interviews conducted with key educational actors in this process. Additionally, articles and editorials from the Israeli and Arab popular presses, which helped to set public opinion on these programs, were examined. This research is important in understanding the conflict between two civic groups who sufferred from ‘the narcissism of minor differences’. This gives hope for the existence of peace.